The Positive Impact of Education, Training, and Work Experience to Influencing Employee Performance - Susana Santi (Universitas Pendidikan Ganesha, 2020)
This study aims to partially and simultaneously analyze the influence of education, training, and work experience factors on employee performance at the Merauke Archdiocese. The data analysis method used in this research is descriptive analysis and multiple linear regression analysis, followed by a test of determination and significance. Data collection techniques used interviews, questionnaires, and literature studies. The population of this study was all 57 employees of the Merauke Archdiocese. The sampling technique used was total sampling. The results of this study indicate that education partially has a positive and significant effect on employee performance with a t-count (2.855) higher than the t-table (2.397). Training partially has a positive and significant effect on employee performance with a t-count (3.027) higher than t-table (2.397). Work experience partially affects employee performance with t-count (3.630) higher than t-table (2.397). Simultaneously education, training, and work experience have a positive and significant effect on employee performance with an F-count (33.443) greater than the F table (3.17). Thus, it can be seen that the most dominant variable that has a significant effect on employee performance is the work experience variable.